2014
DOI: 10.2224/sbp.2014.42.10.1629
|View full text |Cite
|
Sign up to set email alerts
|

How Organizational Embeddedness and Affective Commitment Influence Job Crafting

Abstract: The focus in existing job crafting research has been mainly on employees' perceptions about opportunities to craft their jobs. However, researchers have overlooked the role of emotional attachment to the organization. We examined how organizational embeddedness and affective commitment influence job crafting. To test our model, we surveyed 220 employees working in a manufacturing company in China. The results indicated that organizational embeddedness and affective commitment were both positively related to jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Consistent with the proactivity literature, meta‐analytical and empirical studies showed that general self‐efficacy and core self‐evaluation, the can do motivational state, was positively related to approach crafting (Rudolph et al, ; Tims & Akkermans, ). With regard to reason to motivation states, Qi et al () reported that organizational embeddedness and affective commitment were both positively related to approach crafting, especially when internal social capital was low. Similarly, Moon, Youn, Hur, and Kim () found that employees' spirituality at work, which enables employees to assign meaning to their work experiences, was positively related to approach crafting through increased intrinsic work motivation.…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the proactivity literature, meta‐analytical and empirical studies showed that general self‐efficacy and core self‐evaluation, the can do motivational state, was positively related to approach crafting (Rudolph et al, ; Tims & Akkermans, ). With regard to reason to motivation states, Qi et al () reported that organizational embeddedness and affective commitment were both positively related to approach crafting, especially when internal social capital was low. Similarly, Moon, Youn, Hur, and Kim () found that employees' spirituality at work, which enables employees to assign meaning to their work experiences, was positively related to approach crafting through increased intrinsic work motivation.…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
“…Fourth, a final but important contribution of the hierarchical structure is that it helps to address several concerns with existing job crafting measures. Different versions of crafting measures exist in the literature, even within the same theoretical framework ( combination of approach crafting and avoidance crafting (e.g., Tims et al, 2016;Travaglianti, Babic, & Hansez, 2016;Tuan, 2018), or combination of behavioral crafting and cognitive crafting (e.g., Qi, Li, & Zhang, 2014;Sekiguchi, Li, & Hosomi, 2017), which is problematic for aggregate constructs. To be specific, at the least, crafting measures should distinguish between approach/avoidance and behavioral/cognitive dimensions and represent them properly as formative measures (Figure 1).…”
Section: Figure 2 the Eight Types Of Job Craftingmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, studies specifically addressing links between job crafting and commitment are rare. A study by Qi et al (2014) does, however, link affective commitment to job crafting behaviors in employees in Chinese manufacturing firms, although the study reports on a reverse connection, where affective commitment leads to job crafting. Further, the connection between job crafting and commitment is found in a few papers (Berber et al, 2022;Chang et al, 2020;Leana et al, 2009;Wang et al, 2018;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Although there are few empirical quantitative studies on the association between social capital and job crafting, a study by Qi, Li, and Zhang [35] provides some support. They surveyed 220 employees in a manufacturing company in China using self-report instruments with good reliability and found a rather strong association between social capital and general job crafting.…”
Section: The Role Of Job Craftingmentioning
confidence: 99%